CORRECTION OF BLUE SWIMMING CRAB FOLDING TRAP ENTRANCE: KOREKSI PINTU MASUK BUBU LIPAT RAJUNGAN - Defra Monika Nasution; Gondo Puspito; Didin Komarudin; Mustaruddin Mustaruddin; Deni Aulia (Jurnal Teknologi Perikanan dan Kelautan, 2025)
Folding crab traps are widely used by Indonesian fishermen because they are easy to construct and operate. Observations suggest that crabs frequently struggle to pass through the entrance channel, as their legs become entangled in the mesh. The spines on the sides of their bodies usually become entangled in the net threads because the entrance is too narrow. Consequently, the chance of crabs being trapped is very low. The objective of the study is first to determine the combination of slope angle and mesh size for the channel that allows for crabs to pass through easily. The study attempted to combine the traverse angles of 20°, 30°, and 40° with mesh sizes of 0.125", 0.35", and 1.25". The second objective is to determine the elliptical or rectangular entry gap that is easy for crabs to pass through. Laboratory-scale research and the research data were analysed parametrically using two-way ANOVA and Tukey's post hoc test. The results indicated the combination of an angle of 20° and a mesh size of 0.125" was the best configuration, because 26 individual of crabs could pass through the entry gap. The following combination, 20° (0.35") and 30° (0.125"), each passed through 25 crabs. A total of 369 individual of crabs (63.6%) could pass through the rectangular gap, while 211 individuals (36.4%) passed through the elliptical gap. The combination of a 20° angle and a mesh size of 0.125" with a rectangular entry gap is easier for crabs to pass through compared to other combinations.